2012
DOI: 10.1093/rheumatology/kes067
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and energy expenditure in rheumatoid arthritis patients and matched controls

Abstract: Daily energy expenditure is significantly lower in RA patients compared with matched controls, mainly due to less moderate-intensity PAs performed. Disease activity and fatigue are important contributing factors. These points need to be addressed if promoting PA in RA patients is a health goal. Trial registration. ClinicalTrials.gov, http://clinicaltrials.gov, NCT01228812.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 43 publications
2
28
0
6
Order By: Relevance
“…However, when controlled for potential explanatory variables, only reduced activity due to fatigue, physical fatigue and disease activity were found to be statistically significantly lower in patients being regularly physically active. Findings from this study support previous studies documenting low levels of physical activity and increased sitting time in patients with RA compared to controls [9,[28][29][30]. Although no direct comparison was made in the present study, we found that 27 % of the patients in our study reported being primarily sedentary compared to 16.4 % of the Danish general population [31].…”
Section: Discussionsupporting
confidence: 88%
“…However, when controlled for potential explanatory variables, only reduced activity due to fatigue, physical fatigue and disease activity were found to be statistically significantly lower in patients being regularly physically active. Findings from this study support previous studies documenting low levels of physical activity and increased sitting time in patients with RA compared to controls [9,[28][29][30]. Although no direct comparison was made in the present study, we found that 27 % of the patients in our study reported being primarily sedentary compared to 16.4 % of the Danish general population [31].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies in RA that measured PA (5,18,19,31,32,41,42) did not characterize or measure PA across different intensity categories, and data specifically for participation at light intensities is limited. To date, only 2 studies in RA have reported PA at light intensity, and neither investigated the effect of light-intensity PA on cardiovascular disease risk factors (40,43).…”
Section: Discussionmentioning
confidence: 99%
“…Disease severity, disease activity, and symptoms may also influence PA participation in some rheumatic conditions, 26 although these were not recorded in this study because of challenges in assessing disease severity and activity accurately in the diverse range of rheumatic diseases included.…”
Section: Discussionmentioning
confidence: 99%